Description of Handover Implementation and Early Warning Score Value with Internet System Hospitalization at the Pavilion of One of the Karawaci Private Hospitals - Janwar Olang; Natya Paluwih; Elisabeth Sinulingga; Theresia Agustina (PT FORMOSA CENDEKIA GLOBAL, 2022)
In this very rapidly developing era, the very rapid advancement of information and communication technology is currently bringing big changes in society. The global communication and information exchange system via the internet can be done at any time and without being hindered by distance. The large and growing number of internet users has created internet culture. The Internet also has a major influence on knowledge, and world views. By relying only on search engines like Google, users around the world have easy Internet access to various kinds of information. Compared to books and libraries, the internet represents the extreme decentralization/knowledge of information and data. The early warning score is a tool used by the hospital care team to recognize early signs of clinical deterioration, initiate interventions and increase nurse attention and improve the response of the medical emergency team. This tool involves numerical assignment of several physiological parameters (heart rate, systolic blood pressure, respiration rate, temperature, saturation, consciousness, and urine output) to obtain a composite score to identify patients who are at risk of worsening (Smith, et.al, 2013 )